A master dynamic flow diagram for the shear thickening transition in micellar solutions. Issue 1 (8th October 2015) - Bautista, F.; Tepale, N.; Fernández, V. V. A.; Landázuri, G.; Hernández, E.; Macías, E. R.; Soltero, J. F. A.; Escalante, J. I.; Manero, O.; Puig, J. E.
Abstract : Shear thickening of micellar solutions of hexadecyltrimethylammonium-type surfactants and alkyltretradecylammonium bromide surfactants. A master flow diagram of the shear thickening transition. Intensity of shear thickening and a Hofmeister-like anion series. Abstract : The shear thickening behavior of dilute micellar solutions of hexadecyltrimethylammonium-type surfactants with different counterions (tosylate, 3- and 4-fluorobenzoate, vinylbenzoate and salicylate) and of n -alkyltetradecylammonium bromide (C n TAB), with n = 14, 16 and 18, is examined here. These solutions undergo a shear thickening transition due to the formation of shear-induced structures (SISs) in the shear range studied. Here we report a relationship between the shear thickening intensity and the differences in the hydrophobicity of counterions according to the Hofmeister-like anion series, which leads to a master flow diagram. This master flow diagram is produced by plotting a normalized shear thickening intensity ( I η − 1)/( I max − 1) versus C D / C D, max, where I η is the shear-thickening intensity, defined as the largest viscosity obtained in the shear-thickening transition (STT) at a given surfactant concentration C D divided by the Newtonian viscosity η 0, and I max is the largest intensity value obtained in the STT at a surfactant concentration C D, max . The master flow diagram is built using several cetyltrimethylammonium-type surfactants with different counterions, according to a Hofmeister-like series, and by n -alkyltetradecylammonium bromide surfactants with different alkyl chain lengths.